Medicine as a Scholarly Field: An Introduction - Miettinen, O.S (Springer International Publishing : Imprint: Springer, 2015)
This book exposes, and fills, a notable void in the educational content generally covered in modern schools of medicine. It provides an introduction to the field at large in terms of content that is relevant for each of the specialties and subspecialties of medicine; and to this end, it addresses the modern counterpart of the Hippocratic philosophy that was at the root of the genesis of modern medicine. The much-needed but still-missing introductory content for the interdisciplinary 'medical common,' provided in this book, addresses mainly the most elementary concepts and principles of medicine. Those concepts flow, hierarchically, from the essence of (health and) ill-health/illness for one and that of medicine for another, both of these critically formulated; and those principles are dictates of logic and ethics, both specific to medicine. While a modern physician is expected to be competent as a scholar in his/her particular discipline of medicine, study of this book is essential for the development of that competence -- for learning, for example, to make a tenable distinction between scientific medicine and medical science, and between knowledge-based medicine (scientific and other) and its opinion-based substitutes ('evidence-based' and other). "To me it is astonishing and to medicine actually shameful that it has taken up to year 2015 before there is a work in which the essence of medicine is described and discussed." -- J. Steurer, University of Zurich "[In this book], Miettinen beautifully elucidates the concepts and principles of knowledge-based diagnosis, and prognosis, within medicine. Now, after six decades of keen observation and study, and critical reflection on medicine and medical research, Miettinen, in this book, shares the fundamental understandings he has reached; ..." -- T. J. VanderWeele, Harvard University "The aim of this book ... is admirable. The composition of the book -- from the key concepts to logical and ethical principles -- is very clear and systematic. I am convinced that this kind of book is needed." -- I. Niiniluoto, University of Helsinki.